Zero Energy Building by Multi-Carrier Energy Systems including Hydro, Wind, Solar and Hydrogen - Mehrjerdi, Hasan; Hemmati, Reza; Shafie-khah, Miadreza; Catalao, Joao P. S. (Institute of Electrical and Electronics Engineers, 2020)
This paper proposes a unified solution to address the energy issues in net zero energy building (ZEB), as a new contribution to earlier studies. The multi carrier energy system including hydro-wind-solar-hydrogen-methane-carbon dioxide-thermal energies is integrated and modeled in ZEB. The electrical sector is supplied by hydro-wind-solar, combined heat and power, and pumped hydro storage. The purpose is to minimize the released CO2 to the atmosphere while all the electrical-thermal load demands are successfully supplied following events and disruptions. The model improves the energy resilience and minimizes the environmental pollutions simultaneously. The results demonstrate that the developed model reduces the CO2 pollution by about 33451 kg per year. The model is a resilient energy system that can handle all failures of components and supply both the thermal and electrical loads following events. The model can efficiently handle 26% increment in the electrical loads and 110% increment in the thermal loads.
Keywords: Carbon Dioxide; Multi-Carrier Energy System; Net Zero Energy Building; Renewable to Gas; Thermal Load; fi=Sähkötekniikka|en=Electrical Engineering|